PERKEMBANGAN PESANTREN DI TENGAH DINAMIKA KONFLIK DAN MARAKNYA RADIKALISME PADA KABUPATEN POSO - Ubaidillah Canu; Zainab Canu (Institut Agama Islam Negeri (IAIN) Manado, 2020)
ABSTRACTThis study aims to describe, analyze and interpret the phenomenon of the development of Islamic boarding schools that grow and develop in the midst of the dynamics of conflict that is still happening today, where on the other hand the development of Islamic boarding schools is also marked by the rise of radicalism movements marked by the emergence of armed civilian groups. which was later called the East Indonesia Mujahidin (MIT), this study also aims to explain the alleged relationship between pesantren and radicalism, pesantren with MIT and the allegation of pesantren as a fabrication of radicalism. The method in this study uses a qualitative approach to the type of case study (case study) which emphasizes the ability of the researcher as a key research instrument. The research findings at least explain several things, namely; 1) the development of the pesantren that occurred in Poso began after the conflict of faith where one of the incidents in the conflict was the massacre that occurred at the Walisongo Islamic boarding school in Kilo Sembilan, 2) the radicalism that developed in Poso did not coincide with the motivation for the development of the pesantren, 3) the developing pesantren Poso has no relationship with the MIT group, 4) MIT is purely a combatant group that grows from social ties outside Islamic boarding school education, 5) MIT combatant actors in the investigations conducted by researchers do not come from the pesantren educational environment in Poso, moreover pesantren in Poso is a typology of traditional pesantren which is still said to be very young and not yet established and does not yet have a broad network of regeneration, so it is impossible to become a fabricator of Poso combatants.Keywords: Islamic boarding schools; conflict; radicalism ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan, menganalisis dan menginterpretasikan fenomena perkembangan pesantren yang tumbuh dan berkembang di tengah dinamika konflik yang masih terus terjadi hingga saat ini, di mana pada sisi yang lain perkembangan pesantren juga turut diwarnai dengan maraknya gerakan radikalisme yang ditandai dengan munculnya kelompok sipil bersenjata yang belakangan disebut Mujahidin Indonesia Timur (MIT), penelitian ini juga bertujuan untuk menjelaskan dugaan hubungan pesantren dengan radikalisme, pesantren dengan MIT dan dugaan pesantren sebagai pabrikasi radikalisme. Adapun metode dalam penelitian ini menggunakan pendekatan kualitatif jenis studi kasus (case study) yang menekankan pada kemampuan peneliti sebagai instrumen kunci penelitian. Temuan penelitian setidaknya menjelaskan beberapa hal yaitu; 1) perkembangan pesantren yang terjadi di Poso dimulai paska konflik iman di mana salah satu insiden dalam konflik tersebut adalah pembantaian yang terjadi di pesantren Walisongo di Kilo Sembilan, 2) radikalisme yang berkembang di Poso tidak beriringan dengan motivasi perkembangan pesantren, 3) pesantren yang berkembang di Poso tidak memiliki hubungan dengan kelompok MIT, 4) MIT murni merupakan kelompok kombatan yang tumbuh dari ikatan sosial di luar pendidikan Islam pesantren, 5) aktor-aktor kombatan MIT dalam investigasi yang peneliti lakukan tidak berasal dari lingkungan pendidikan pesantren di Poso, lagipula pesantren di Poso merupakan tipologi pesantren tradisional yang masih dikatakan sangat belia dan belum mapan serta belum memiliki jaringan kaderisasi yang luas, sehingga sangat mustahil untuk dapat menjadi pabrikasi kombatan Poso.Kata Kunci: Pesantren; Konflik; Radikalisme